PENERAPAN SUPERVISI AKADEMIK SEBAGAI UPAYA PENINGKATAN PEMBELAJARAN DI KELAS: Implementation Of Academic Supervision As An Improvement Effort Learning In The Class - Nurmayuli; Aini Safitri; Sinta Ulandari (Program Studi Manajemen Pendidikan Islam, 2023)
After the Covid 19 pandemic, when online learning switched to offline or face-to-face. Face-to-face learning in the classroom requires positive energy, not only from presenting material technologically, but teachers can display learning that is energetic and sweet. Energetic and dynamic learning is expected to stimulate the affective, psychomotor and motor development of students so as to enhance learning in class. Application of academic supervision by supervisors to teachers as an effort to improve learning in the classroom. Supervision is carried out through the approach of 4 (four) academic supervision models which include Snoopervision, scientific, clinical and artistic models. Then the academic supervision techniques used individual and group techniques.